2020
DOI: 10.1016/j.jaccas.2019.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Circulatory Support for the Management of Complex Peripartum Cardiomyopathy

Abstract: Peripartum cardiomyopathy (PPCM) is a rare but potentially fatal disease. The management of PPCM is individualized, and an early diagnosis is instrumental in the institution of an appropriate management plan. Here, we present a dramatic case of PPCM that was managed with a period of mechanical circulatory support. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…MCS devices are used in CS with severe hemodynamic compromise refractory to medical therapy, sometimes as a bridge to a durable VAD or HT . The evidence on the association of MCS use compared with medical therapy with mortality in PPCM is variable and limited by small observational studies, case series, and reports . We found worse mortality outcomes in Black and Hispanic patients compared with White patients, despite relatively higher MCS utilization rates.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…MCS devices are used in CS with severe hemodynamic compromise refractory to medical therapy, sometimes as a bridge to a durable VAD or HT . The evidence on the association of MCS use compared with medical therapy with mortality in PPCM is variable and limited by small observational studies, case series, and reports . We found worse mortality outcomes in Black and Hispanic patients compared with White patients, despite relatively higher MCS utilization rates.…”
Section: Discussionmentioning
confidence: 68%
“…40,41 The evidence on the association of MCS use compared with medical therapy with mortality in PPCM is variable and limited by small observational studies, case series, and reports. [42][43][44][45][46][47][48] We found worse mortality outcomes in Black and Hispanic patients compared with White patients, despite relatively higher MCS utilization rates. This paradox may be explained by more severe disease refractory to the benefit of circulatory support devices among Black and Hispanic patients with PPCM and CS.…”
Section: Jama Network Open | Cardiologymentioning
confidence: 59%
“…2 In summary, we describe the successful use of pRVAD support for cesarean delivery in a patient with severe PAH. Although use of MCS for peripartum cardiomyopathy 15 and amniotic fluid embolism have been reported, 9 our report adds to these by describing pRVAD use in the context of RV failure after cesarean delivery. In our patient, early recognition of worsening RV function with rapid pRVAD placement after delivery likely reduced the risk of cardiogenic shock and end-organ dysfunction.…”
Section: Discussionmentioning
confidence: 86%
“…Previously published systematic reviews and case series have primarily reported on CS occurring in later pregnancy or postpartum. 4 , 5 , 6 , 7 Our case is unique in describing our multidisciplinary approach in managing CS in early pregnancy, before a high likelihood of fetal survival, with the early initiation of MCS as a bridge to durable LVAD and showing that favorable outcomes for both mother and child can be achieved.…”
Section: Discussionmentioning
confidence: 96%